Optical Coherence Tomography Angiography in Glaucoma: A Review - Van Melkebeke, Lukas; Barbosa-Breda, João; Huygens, Marc; Stalmans, Ingeborg (Ophthalmic research, 2018)
Glaucoma is the leading cause of irreversible blindness worldwide. Several techniques exist for the diagnosis and follow-up of patients. Optical coherence tomography (OCT) angiography (OCTA) is a recently developed technique that provides a quantitative assessment of the microcirculation of the retina and choroid in a fast, noninvasive way. Despite it being a novel technique, several publications have already been done in the glaucoma field. However, a summary of findings is currently lacking. To perform a literature review to assess the role of OCTA in glaucoma diagnosis and follow-up. A database search was carried out using MEDLINE, Embase, and Web of Science, including all original works registered until July 23, 2017. OCTA (1) has a high repeatability and reproducibility, (2) has good discriminatory power to differentiate normal eyes from glaucoma eyes, (3) is more strongly correlated with visual function than conventional OCT, (4) has good discriminatory power to differentiate early-glaucoma eyes from normal eyes (i.e., at least equal to that of OCT), (5) reaches a floor effect at a more advanced disease stage than OCT, and (6) is able to detect progression in glaucoma eyes. OCTA shows potential to become a part of everyday glaucoma management.